2017
DOI: 10.1038/s41598-017-16175-x
|View full text |Cite
|
Sign up to set email alerts
|

MiR-30e inhibits tumor growth and chemoresistance via targeting IRS1 in Breast Cancer

Abstract: MicroRNA-30e (miR-30e) is downregulated in various tumor types. However, its mechanism in inhibiting tumor growth of breast cancer remains to be elucidated. In this study, we found that miR-30e was significantly downregulated in tumor tissues of breast cancer (BC) patients and cell lines, and overexpression of miR-30e inhibited cell proliferation, migration and invasion. To understand the potential mechanism of miR-30e in inhibiting tumor growth, we showed that miR-30e blocked the activation of AKT and ERK1/2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 33 publications
1
35
0
Order By: Relevance
“…Wang et al suggested that lncRNA CPS1-IT1 could serve as an Hsp90 cochaperone, and this interaction in turn reduces the binding affinity between Hsp90 and HIF-1α, leading to transcriptional inactivation of HIF-1α and diminished EMT of hepatocellular carcinoma cells [135]. In addition, the lncRNA-mediated regulation of the mTOR/HIF-1α/P-gp signaling pathway marked by increased HIF-1a mRNA [146] miR-23b glioma promotes proliferation and migration, inhibits apoptosis post-translational activation via VHL [147] miR-145 colorectal cancer inhibits proliferation, migration and invasion post-translational inhibition via Akt/ERK axis [148] miR-30e breast cancer inhibits proliferation, migration and invasion post-translational inhibition via IIRS1/Akt/ERK axis [149] miR-26a hepatocellular cancer inhibits angiogenesis post-translational inhibition via PIK3C2α/Akt axis [150] miR-99a breast cancer inhibits migration, invasion, sphere formation post-translational inhibition via mTOR signals [151] lncRNA ENST00000480739…”
Section: Transcriptional Regulation Of Hif-1α Expression By Ncrnasmentioning
confidence: 99%
“…Wang et al suggested that lncRNA CPS1-IT1 could serve as an Hsp90 cochaperone, and this interaction in turn reduces the binding affinity between Hsp90 and HIF-1α, leading to transcriptional inactivation of HIF-1α and diminished EMT of hepatocellular carcinoma cells [135]. In addition, the lncRNA-mediated regulation of the mTOR/HIF-1α/P-gp signaling pathway marked by increased HIF-1a mRNA [146] miR-23b glioma promotes proliferation and migration, inhibits apoptosis post-translational activation via VHL [147] miR-145 colorectal cancer inhibits proliferation, migration and invasion post-translational inhibition via Akt/ERK axis [148] miR-30e breast cancer inhibits proliferation, migration and invasion post-translational inhibition via IIRS1/Akt/ERK axis [149] miR-26a hepatocellular cancer inhibits angiogenesis post-translational inhibition via PIK3C2α/Akt axis [150] miR-99a breast cancer inhibits migration, invasion, sphere formation post-translational inhibition via mTOR signals [151] lncRNA ENST00000480739…”
Section: Transcriptional Regulation Of Hif-1α Expression By Ncrnasmentioning
confidence: 99%
“…The miR-30 family, which contains five members of distinct pre-mature miRNAs (miR-30a, -30b, -30c, -30d, -30e), has been proved to play diverse roles in regulating essential aspects of tumorigenesis, metastasis, chemo-resistance and clinical prognosis in several types of human cancers [11,12]. A large number of reports have demonstrated that miR-30a-5p, as a member of the mir-30 family, was down-regulated and associated with tumorigenesis and progression of prostate cancer, hepatocellular carcinoma, breast tumor and some other cancers [13][14][15].…”
Section: Ivyspring International Publishermentioning
confidence: 99%
“…To mechanistically determine the role of miR-126 in HCC development and progression, we predicted the target genes of miR-126 using the bioinformatics algorithm TargetScan website. MiR-126 has a putative binding site from 106~112 bp within the 3′-UTR region of IRS1 gene (Figure 2 a), whose product (IRS1 protein) was reported to promote tumor growth and chemoresistance [13][14][15]. To verify this speculation, we transfected miR-126 mimics into two HCC cell lines HCCLM3 and MHCC-97H, and found that both mRNA and protein levels of IRS1 were significantly inhibited upon miR-126 overexpression (Figure 2 b and c).…”
Section: Mir-126 Represses the Expression Of Irs1mentioning
confidence: 99%